1998
DOI: 10.1046/j.1464-410x.1998.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting regional lymph node metastasis in carcinoma of the penis: a comparison between fine‐needle aspiration cytology, sentinel lymph node biopsy and medial inguinal lymph node biopsy

Abstract: Objective  To evaluate the accuracy of clinical examination and fine‐needle aspiration cytology (FNAC) in detecting groin metastases in patients with carcinoma of the penis, and to assess the positive and negative predictive value (PPV, NPV) of a preliminary sentinel lymph‐node biopsy (SNB) and biopsy of the most medial of the horizontal group of inguinal lymph nodes (MIN) in selecting patients for an ilio‐inguinal block dissection. Patients and methods  The study comprised 28 patients (56 groins) with Stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…False‐positive results for metastatic lymphadenopathy in primary penile cancer have rarely been reported using FNA cytology [8,10,28], but there was one case in the present series. Although some centres, including ours, have advocated routine inguinal dissection where there is palpable lymphadenopathy, this policy results in some cases where metastatic disease is not identified.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…False‐positive results for metastatic lymphadenopathy in primary penile cancer have rarely been reported using FNA cytology [8,10,28], but there was one case in the present series. Although some centres, including ours, have advocated routine inguinal dissection where there is palpable lymphadenopathy, this policy results in some cases where metastatic disease is not identified.…”
Section: Discussionmentioning
confidence: 61%
“…It is well recognised that clinical examination of groin nodes for metastases is inaccurate [10], as in the present study, yet the reported incidence of inguinal LN metastases in penile cancer is 40–50%[4]. The inguinal nodes are the initial drainage point for the lymphatics of the penis, and it is generally accepted that all men with primary SCC of the penis where such nodal metastases are present should be treated by inguinal LND [11].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Ravi et al [28] performed an ''inguinal pick procedure'' in 52 patients, which included biopsy of all suspicious nodes and removal of nodes in the ''sentinel node area'': 5 of 52 patients (9.6%) had nodal metastasis; notably, 7 of 47 patients (15%) with negative histology developed inguinal lymph node recurrence. Senthil-Kumar et al [29] investigated 28 patients undergoing groin dissection; clinically nodenegative patients underwent dissection of the most medial lymph nodes of the inguinal region, and in 20 patients with node-negative disease the specificity and positive predictive values were 100%.…”
Section: Urologic Malignancies Penile Cancermentioning
confidence: 99%